Market Competition and Efficient Cooperation - Jordi Brandts; Arno Riedl (Center for Economic Studies and ifo Institute (CESifo), 2016)
We use laboratory experiments to study the causal effects of favorable and unfavorable competitive market experience on cooperation in a subsequent social dilemma game. The issues we study are part of the broader topic of whether there are behavioral spillovers between different spheres of social interactions. Market interaction takes place in a continuous double auction market in which one side of the market obtains the larger part of the surplus. We examine the efficiency of subsequent cooperation for pairs of market-winners, market-losers and mixed pairs and study both the cases where interaction in the social dilemma is with others from the same market, `market-partners', and where it is with others from another market, `market-strangers', and compare it with benchmark behavior in a stand-alone social dilemma game. We find that in market-partners, market experience has adverse effects on the efficiency of cooperation on both market-winner and market-loser pairs. In market-strangers, pairs of market-winners manage to cooperate more efficiently. These results indicate that it is not market experience per se that lowers the ability to cooperate. Rather, having competed for scarce resources on the same side of the market makes it difficult to overcome the social dilemma and positive market experience fosters cooperation only for those who did not have to compete with each other. We also show that differences in cooperation cannot be explained by ex-ante income differences and find that market experience also affects subjective well-being and social value orientation.
Keywords: A13; C92; D30; J50; M50; 330; competition; cooperation; experiments